Effects of Level of Control on Simulator Sickness Using a Virtual Reality Head Mounted Device - Merta, Michael; Kelling, Nicholas (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 2015)
Virtual Reality (VR) devices have remained primarily within the medical and military field for occupational training with varying success while personal VR usage for entertainment has been relatively stagnant. This trend is expected to change with VR head mounted devices (HMD) being targeted by several tech businesses such as Facebook and Samsung. The current study focuses on three different types of control levels: high, medium, and low. Each of these is categorized based on the amount of interactivity allowed within the VR application. Participants (n=12) took part in a within-subjects experiment where they used three programs and reported feelings of simulation induced motion sickness, or simulation sickness, for each one. Results identified significant differences between the programs. Factors related to VR accommodation are discussed.